2017
DOI: 10.1073/pnas.1620315114
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation by PKC and PKA regulate the kinase activity and downstream signaling of WNK4

Abstract: With-no-lysine kinase 4 (WNK4) regulates electrolyte homeostasis and blood pressure. WNK4 phosphorylates the kinases SPAK (Ste20-related proline alanine-rich kinase) and OSR1 (oxidative stress responsive kinase), which then phosphorylate and activate the renal Na-Cl cotransporter (NCC). WNK4 levels are regulated by binding to Kelch-like 3, targeting WNK4 for ubiquitylation and degradation. Phosphorylation of Kelch-like 3 by PKC or PKA downstream of AngII or vasopressin signaling, respectively, abrogates bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 51 publications
(68 reference statements)
0
55
0
Order By: Relevance
“…Therefore, hormones that regulate the PKA pathway could potentially be involved in the regulation of NCC SV -mediated Na + transport in DCT. There is a growing body of evidence that demonstrates that NCC abundance and phosphorylation is affected by PKC or PKA downstream of angiotensin II or vasopressin signaling, respectively (43,(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hormones that regulate the PKA pathway could potentially be involved in the regulation of NCC SV -mediated Na + transport in DCT. There is a growing body of evidence that demonstrates that NCC abundance and phosphorylation is affected by PKC or PKA downstream of angiotensin II or vasopressin signaling, respectively (43,(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Besides these mechanisms, there is also evidence that AngII modulates WNK function (SanCristobal et al 2009). Of note, a recent study identified WNK4 sites that are phosphorylated downstream of AngII signaling (Castaneda-Bueno et al 2017). Interestingly, AngII phosphorylation of WNK4 modulates WNK4 kinase activity by promoting autophosphorylation of S332 of the T-loop in the kinase catalytic domain.…”
Section: Mechanisms Regulating Ncc In Dct Cellsmentioning
confidence: 99%
“…30,31 This regulation occurs via protein kinase C (PKC), which directly phosphorylates WNK4 in two main sites, S64 and S1196, increasing WNK4 activity. 32 PKC also promotes phosphorylation of KLHL3 in a serine residue (S433) that lays in the WNK4-binding domain preventing degradation of WNK4. 33 The effects of AngII in the DCT are mediated by the AT1 receptor, a pleiotropic GPCR whose intracellular signaling mechanisms are similar to that of CaSR.…”
mentioning
confidence: 99%